PERENCANAAN PENYEDIAAN AIR MINUM BERBASIS MASYARAKAT DI DUSUN TOMUAN PANE, KABUPATEN SIMALUNGUN, SUMATERA UTARA - Andika, Ida Bagus Made Baskara; Nainggolan, Kristina Marta; Astiti, Sagung Putri Chandra (Program Studi Magister Teknik Sipil Universitas Udayana, 2026)
Tomuan Pane Hamlet in Simalungun Regency, North Sumatra, faces critical challenges in drinking water provision due to the absence of a household water distribution network. Additionally, water quality tests revealed phosphate and total coliform contamination levels exceeding the drinking water standards set by the Indonesian Ministry of Health Regulation No. 2 of 2023. The contamination is attributed to nearby agricultural activities and poorly maintained environmental infrastructure. This study aims to design a simple, community-based water distribution and treatment system (Penyediaan Air Minum Berbasis Masyarakat: PAMBM). Water demand projections were calculated using three population growth methods: arithmetic, geometric, and least square approaches. The distribution network was simulated using EPANET 2.2 software. The water treatment system was designed utilizing simple filtration tailored to local conditions. Population projections indicate that water demand in 2040 will reach 0.88 L/s. The proposed treatment system consists of two filtration stages: a 1.2-meter downflow reactor of 67% zeolite, 8% sand, 8% activated carbon media, and a 2-meter upflow reactor of 21% zeolite, 21% gravel, 27% activated carbon, and 21% sand media:. The combined system effectively reduced phosphate concentrations by 49.39% and completely eliminated total coliforms (100% removal). The distribution network simulation produced an average flow velocity of 0.71 m/s using a 5 cm transmission pipe and a 4 cm main distribution pipe.